Management of collar rot of groundnut (Arachis hypogaea) by fungicides and mineral nutrients - BAJAYA, TEJPAL; GHASOLIA, R P; BAJYA, MAMTA; SHIVRAN, MANISHA (The Indian Journal of Agricultural Sciences, 2022)
Collar rot disease caused by Aspergillus niger van Teighem is an important seed and soil borne disease of groundnut (Arachis hypogaea L.) which deteriorates kernel quality and reduces yield. The experiments were conducted during kharif 2019 and 2020 at SKN College of Agriculture, Jobner, Jaipur, Rajasthan. To see the interactive effect of seed treatment and drenching, fungicides and bio-agents were applied through seeds [carbendazim (0.1%), carboxin+ thiram (0.25%), hexaconazole (0.2%), carbendazim + mancozeb (0.25%), Trichoderma harzianum (0.6%) and Trichoderma viride (0.6%)] and through drenching [carbendazim (0.1%), carboxin + thiram (0.25%) and carbendazim + mancozeb (0.25%)] at 20 days after sowing (DAS). The effect of six mineral nutrients i.e. Cu (5 kg/ha), K (30 kg/ha), S (25 kg/ha), B (10 kg/ha), Fe (5 kg/ha) and Zn (5 kg/ha) was also evaluated through soil application against the disease. The lowest disease incidence (4.62%) and highest pod yield (25.86 q/ha) were recorded by treating the seeds with hexaconazole (@0.2%) and drenching with carbendazim + mancozeb (@0.25%) at 20 DAS and next best was seed treatment with hexaconazole (0.2%) and drenching with carbendazim (0.1%). Among six mineral nutrients, copper (@5 kg/ha) was most significant in reducing the disease incidence (46.05%) and in increasing pod yield (24.81%) followed by potassium. Conclusively, seed treatment with hexaconazole (@0.2%) and drenching with carbendazim + mancozeb (@0.25%) at 20 days after sowing results in significantly higher disease control with increased pod yield.